2014
DOI: 10.1371/journal.pone.0084547
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Molecular Profiling of PSEN1 Familial Alzheimer's Disease iPSC-Derived Neural Progenitors

Abstract: Presenilin 1 (PSEN1) encodes the catalytic subunit of γ-secretase, and PSEN1 mutations are the most common cause of early onset familial Alzheimer's disease (FAD). In order to elucidate pathways downstream of PSEN1, we characterized neural progenitor cells (NPCs) derived from FAD mutant PSEN1 subjects. Thus, we generated induced pluripotent stem cells (iPSCs) from affected and unaffected individuals from two families carrying PSEN1 mutations. PSEN1 mutant fibroblasts, and NPCs produced greater ratios of Aβ42 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 51 publications
7
118
0
Order By: Relevance
“…On the contrary, no accumulation of tau protein was observed in this type of FAD-derived neurons, revealing that at least for that genotype this protein may not be the main cause of ailment [12,15,20]. Indeed, some studies have showed that iNs and iPSCs-derived neurons from FAD patient fibroblasts had an increased Aβ42/Aβ40 ratio that resembles that observed in AD brains [10,21,22]. Similarly, human iNs from familial AD patients recapitulated the pathology of altered processing and aberrant endosomal localization of APP as well as increased production of Aβ peptides [23].…”
Section: Discussionmentioning
confidence: 73%
“…On the contrary, no accumulation of tau protein was observed in this type of FAD-derived neurons, revealing that at least for that genotype this protein may not be the main cause of ailment [12,15,20]. Indeed, some studies have showed that iNs and iPSCs-derived neurons from FAD patient fibroblasts had an increased Aβ42/Aβ40 ratio that resembles that observed in AD brains [10,21,22]. Similarly, human iNs from familial AD patients recapitulated the pathology of altered processing and aberrant endosomal localization of APP as well as increased production of Aβ peptides [23].…”
Section: Discussionmentioning
confidence: 73%
“…In one study, no tau accumulation or tangle formation was observed [51]. One other study has reported small changes in gene function in PSEN1 mutant iPSC-derived neurons, including increased NLRP2, ASB9 and NDP [53]. In addition, overexpression of PSEN1 in human ESCs led to increased Aβ42/Aβ40 and Aβ43/Aβ40 ratios as well as synaptic dysfunction in neurons expressing NeuN and BIII-tubulin [56].…”
Section: Psen1 Mutationsmentioning
confidence: 96%
“…These studies have revealed that most of the neurons generated from PSEN1 AD patients also have increased Aβ42 [51][52][53][54], although decreases in Aβ40 have also been described in two particular mutations [55]. However, little other pathology has been described.…”
Section: Psen1 Mutationsmentioning
confidence: 99%
“…[39][40][41] Pluripotent stem cells (PSCs) are primarily used as the cell source due to their capacity for self-organization through processes of self-assembly, self-patterning, and self-driven morphogenesis. [42][43][44] Independent of the approach used to develop 3D printing models, accurately recapitulating key aspects of the in vivo environment remains a major challenge. [45][46][47][48] A fundamental understanding of native tissues and organs is first needed before mimicking these in in vitro cultures.…”
Section: Engineering Technologiesmentioning
confidence: 99%